2013
DOI: 10.1002/0471142700.nc0130s52
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Novel 5′‐Regioselective Phosphitylating Reagent for One‐Pot Synthesis of Nucleoside 5′‐Triphosphates from Unprotected Nucleosides

Abstract: The 5′-triphosphates are the building blocks for the enzymatic synthesis of DNAs and RNAs. This unit presents a protocol for the convenient synthesis of 2′-deoxyribo- and ribo-nucleoside 5′-triphosphates (dNTPs and NTPs) containing all the natural bases and the modified bases. This one-pot synthesis can also be applied to prepare the triphosphate analogs that contain sulfur or selenium atoms replacing the non-bridging oxygen atoms of the alpha phosphates of the triphosphates. These S- or Se-modified dNTPs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Based on modification of previously described methods, 20 the unprotected L-nucleoside (~0.7 mmol) was dissolved in 2 mL of either DMF (for C and U) or 1:1 DMF:DMSO (for A and G) in a flask containing activated molecular sieves, then stirred at 23 °C for 2 h. In a separate flask, also containing activated molecular sieves, 3 mL DMF, 0.14 mmol tributylammonium pyrophosphate, 0.85 mmol 2-chloro-4-H-1,2,3-benzodioxaphosphorin-4-one, and 0.5 mL tributylamine were added sequentially and stirred at 23 °C for 2 h. The pyrophosphate solution then was added slowly to the nucleoside solution at 4 °C and the reaction was allowed to proceed for 3 h before adding ~10 mL of 0.1 M iodine in THF/water/pyridine until a persistent brown color appeared. After 1 h, 10 mL of water was added to the mixture, which was stirred at 23 °C for 1 h. The NTP was recovered by ethanol precipitation, then purified by HPLC on a 250 × 10 mm Luna C18 column (Phenomenex, Torrance, CA) using a linear gradient of 0–10% acetonitrile in 20 mM triethylammonium acetate (pH 7.0), with UV detection at 254 nm.…”
Section: Online-only Methodsmentioning
confidence: 99%
“…Based on modification of previously described methods, 20 the unprotected L-nucleoside (~0.7 mmol) was dissolved in 2 mL of either DMF (for C and U) or 1:1 DMF:DMSO (for A and G) in a flask containing activated molecular sieves, then stirred at 23 °C for 2 h. In a separate flask, also containing activated molecular sieves, 3 mL DMF, 0.14 mmol tributylammonium pyrophosphate, 0.85 mmol 2-chloro-4-H-1,2,3-benzodioxaphosphorin-4-one, and 0.5 mL tributylamine were added sequentially and stirred at 23 °C for 2 h. The pyrophosphate solution then was added slowly to the nucleoside solution at 4 °C and the reaction was allowed to proceed for 3 h before adding ~10 mL of 0.1 M iodine in THF/water/pyridine until a persistent brown color appeared. After 1 h, 10 mL of water was added to the mixture, which was stirred at 23 °C for 1 h. The NTP was recovered by ethanol precipitation, then purified by HPLC on a 250 × 10 mm Luna C18 column (Phenomenex, Torrance, CA) using a linear gradient of 0–10% acetonitrile in 20 mM triethylammonium acetate (pH 7.0), with UV detection at 254 nm.…”
Section: Online-only Methodsmentioning
confidence: 99%
“…222 This method has also been applied to the synthesis of base-modified NTPs 108,223−225 and sugar-modified NTPs. 224 In 2011−2013, the Huang research group reported a method based on the hypothesis that a bulky phosphitylation reagent would react selectively with the primary 5′-OH group versus the secondary 2′-and 3′-OH groups, 185,186,226,227 thus avoiding extra steps of synthesis (introduction and removal of protecting groups). New reagent 183 was generated in situ through the reaction of salicylic chlorophosphite 180 with excess tetra(tri-nbutylammonium) pyrophosphate (Scheme 29).…”
Section: Nucleoside 5′-triphosphatesmentioning
confidence: 99%
“…Since then, several reviews , and chapters in books ,, have focused on the subject. However, these reports only partially cover solid support synthesis, and in recent years, a number of relevant synthetic approaches have also emerged. ,, Similarly to NDPs, synthesis of NTPs relies on P­(III) and/or P­(V) intermediates (Figure ) and involves the nucleoside or nucleoside 5′-monophosphates as the starting material. In all cases, anhydrous conditions are essential to avoid the generation of byproducts formed by side reactions with water.…”
Section: Nucleoside 5′-triphosphatesmentioning
confidence: 99%
“…Another strategy, designed by Caton-Williams et al (Caton-Williams et al, 2011a , b , 2013 ), also makes use of the salicyl phosphorochloridite reagent, but through and altered route. In this synthetic scheme the phosphitylating agent is first treated with pyrophosphate in DMF to generate the actual phosphitylating reagent that regioselectively reacts with the 5′-hydroxyl of an unprotected nucleoside to produce a similar cyclic intermediate to the one formed in the Ludwig-Eckstein strategy.…”
Section: Modified Nucleoside Triphosphate Synthesismentioning
confidence: 99%